LITERATURE REVIEW : POLA HIDUP SEHAT SESUAI SUNNATULLAH - Sulaeman, Sulaeman (Journal Medical Kuningan, 2024)
Health is an important component in supporting a person’s productivity and every individual need healthy for their survival. This literature study aims to determine the Islamic view on body health according to Sunnatullah. This study was conducted using the literature review method using the Pubmed and Google Scholar database with the keyword health, sunnatullah, and islam. The inclusion criteria for this literature are articles published in the last 10 years, in English or Indonesia, health intervention studies and sunnatullah, articles that can be accessed online. Articles are selected individually through a double process by considering three main criteria for research quality. The results of the study show that Islamic teachings provide positive benefits for health through emphasizing mental health, and regulating healthy lifestyles.